2003
DOI: 10.1007/s00270-003-2690-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Ultrasound-Based Navigation Combined with Preoperative CT During Abdominal Interventions: A Feasibility Study

Abstract: Preoperative CT in combination with 3D ultrasound might be helpful for guiding minimal invasive abdominal interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
0
32
0
1
Order By: Relevance
“…Since fast and precise automatic algorithms for non-rigid intraoperative registration of 3D ultrasound data are still under development, for neurosurgery Lindseth et al [6] suggested only to rigidly register preoperative data, trust on ultrasound navigation and use the preoperative data as an orientation aid. Applications in abdominal interventions which make use of preoperative image data to augment navigated intraoperative ultrasound scans include: laparoscopy [7,8] for better orientation and thermal ablation of liver lesions [9,10] for precise placement of preplanned applicator positions. Fast and robust intraoperative registration is the crucial task for augmenting the ultrasound data.…”
Section: Introductionmentioning
confidence: 99%
“…Since fast and precise automatic algorithms for non-rigid intraoperative registration of 3D ultrasound data are still under development, for neurosurgery Lindseth et al [6] suggested only to rigidly register preoperative data, trust on ultrasound navigation and use the preoperative data as an orientation aid. Applications in abdominal interventions which make use of preoperative image data to augment navigated intraoperative ultrasound scans include: laparoscopy [7,8] for better orientation and thermal ablation of liver lesions [9,10] for precise placement of preplanned applicator positions. Fast and robust intraoperative registration is the crucial task for augmenting the ultrasound data.…”
Section: Introductionmentioning
confidence: 99%
“…Their increasing popularity may result in more navigation systems applying this imaging modality in the future [29]. Currently, however, only few endoscopic navigation systems for heart interventions [50], [42], [68] or aortic stent implantation [53] acquire volume data directly by 3D ultrasound. Additionally, Baumhauer et al [7] presented an approach for navigated laparoscopic radical prostatectomy, which is based on the intraoperative processing of 3D transrectal ultrasound volumes.…”
Section: Current Approaches For Soft Tissue Navigation In Endoscmentioning
confidence: 99%
“…But not only guidance information is used to enrich ultrasound images. Kaspersen et al [53] utilize preoperative CT segmentations to augmented intraoperative 3D ultrasound data for navigated stent implantation of the aorta. Linte et al [68] visualize their navigated mitral valve implantation by an augmented 3D visualization.…”
Section: Organ Shift and Tissue Deformationmentioning
confidence: 99%
“…6.). Kaspersen et al (2003) reported a feasibility study registering ultrasound acquired during EVAR to pre-acquired CT data. This may be useful for updating the CT data used for navigation due to e.g.…”
Section: Ultrasound In Endovascular Treatmentmentioning
confidence: 99%